UPAYA PENINGKATAN DISIPLIN BELAJAR SISWA MELALUI MANAJEMEN WAKTU DI SD LABAN TENGAH - Fayza Salsabilla; Putri Ayu Arofiq; Hamidah Hamidah (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The purpose of this service activity is to provide counseling on time management and to improve the discipline of elementary school students in Laban Tengah, Tirtayasa District, Serang Regency. The service method used is in the form of offline counseling which is carried out to grade 6 students at SD Laban Tengah totaling 49 students. The instruments used for evaluation are a questionnaire of student responses to counseling given after the counseling is completed and as well as a questionnaire of teacher responses to counseling given 2 weeks after the counseling activity is completed.  The data analysis uses the percentage of responses and determines the category of those responses. The results and conclusions of the counseling activities are: 1) the student response to the counseling  activity is 89%, which is classified as very good.  In other words, students consider counseling activities to make an excellent contribution to their knowledge of the importance of time management and discipline; 2)  the teacher's response to counseling  activities is 86%, which is classified as very baik. According to the teacher, there are changes in students' daily activities after this counseling, students can also make their daily schedules to get used to discipline